ANALISIS PEMBUKTIAN PENUNTUT UMUM PADA TINDAK PIDANA NARKOTIKA (STUDI PUTUSAN NOMOR : 22/PID.SUS/2022/PN.KRG - Al Islami, Silvia Meilani; Rustamaji, Muhammad (Verstek, 2023)
This research aims to determine the suitability of the Public Prosecutor's evidentiary construction in proving drug abuse for dealers inVerdictNumber 22/Pid.Sus/2022/PN Krg with the evidentiary law. This research is normative or doctrinal legal research. The nature of this research is perscriptive and applied. The approach used in this study is the case approach. The legal materials used are primary legal materials and secondary legal materials. The legal material collection technique used in this study is a literature study. The legal material analysis technique used is a syllogism method with a deductive mindset, which is based on a major premise and a minor premise which is then drawn conclusions.Based on this research, the results were obtained that the construction of proof of the Public Prosecutor in proving drug abuse for dealers in VerdictNumber 22/Pid.Sus/2022/PN Krg has been in accordance with the evidentiary law.Keywords: Proof; Narcotics;Verdict